2005
DOI: 10.1308/1478708051847
|View full text |Cite
|
Sign up to set email alerts
|

Intra-operative peritoneal lavage – who does it and why?

Abstract: INTRODUCTION Intra-operative peritoneal lavage (IOPL) is widely practised but its benefits are unclear. The frequency and pattern of its use amongst general surgeons is investigated.METHODS A postal questionnaire was sent to 153 general surgical consultants and registrars enquiring about their use of IOPL. The surgeon was asked the volume and type of lavage fluid used, under various circumstances.RESULTS 118 (77%) questionnaires were returned. 115 (97%) surgeons used IOPL. The majority of surgeons (61%) lavage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
59
2
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(72 citation statements)
references
References 21 publications
(18 reference statements)
1
59
2
5
Order By: Relevance
“…Despite the controversy surrounding the efficacy of peritoneal lavage in the medical literature 17,18 , our present experiment has shown that peritoneal lavage does lower mortality. The local anesthetics increase survival in several studies on experimental models with mice 19 and dogs 20 even when administered systemically.…”
Section: Discussioncontrasting
confidence: 46%
“…Despite the controversy surrounding the efficacy of peritoneal lavage in the medical literature 17,18 , our present experiment has shown that peritoneal lavage does lower mortality. The local anesthetics increase survival in several studies on experimental models with mice 19 and dogs 20 even when administered systemically.…”
Section: Discussioncontrasting
confidence: 46%
“…Nevertheless, it is known that peritoneal washing in peritonitis is a controversial issue. although peritoneal washing is utilized by a large number of surgeons 23 . Peritoneal washing with physiological saline of peritonitic rats, evoked lower mortality compared to plain cleaning of the cavity with compresses 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Although lavage during laparoscopy is more efficient than during laparotomy [3], its usefulness remains controversial [4][5][6][7]. Over the last years, extensive peritoneal lavage during laparoscopy was reported to be useful for the treatment of complications following colorectal surgery and for diverticulitis [8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%